(untitled) (The Review of Diabetic Studies, 2025)
This systematic review examines the critical role of paramedics in delivering pre-hospital interventions within emergency medical services (EMS). Pre-hospital care is often the determining factor between life and death in time-sensitive emergencies such as cardiac arrest, trauma, stroke, and respiratory distress. Paramedics, as frontline responders, implement interventions ranging from airway management and cardiopulmonary resuscitation (CPR) to advanced life support procedures, medication administration, and trauma stabilization. The review synthesizes findings from peer-reviewed studies (2015–2025) to evaluate the effectiveness, challenges, and outcomes associated with paramedic-led pre-hospital interventions. Results indicate that timely and evidence-based interventions provided by paramedics significantly improve survival rates, reduce complications, and optimize patient flow into hospitals. However, challenges such as variability in training, resource availability, and integration with hospital systems remain barriers. The study highlights paramedics’ evolving role in modern healthcare systems and emphasizes the need for continuous education, technological integration, and standardized protocols. This review provides insights for healthcare policymakers, educators, and EMS organizations to enhance pre-hospital emergency care, ultimately strengthening healthcare systems and saving lives.